Preconditioning is hormesis part I: Documentation, dose-response features and mechanistic foundations. (August 2016) - Calabrese, Edward J.
Graphical abstract: Abstract: This article provides the first extensive documentation of the dose response features of pre- and postconditioning. Pre- and postconditioning studies with rigorous study designs, using multiple doses/concentrations along with refined dose/concentration spacing strategies, often display hormetic dose/concentration response relationships with considerable generality across biological model, inducing (i.e., conditioning) agent, challenging dose treatment, endpoint, and mechanism. Pre- and postconditioning hormesis dose/concentration-response relationships are reported for 154 diverse conditioning agents, affecting more than 550 dose/concentration responses, across a broad range of biological models and endpoints. The quantitative features of the pre- and postconditioning-induced protective responses are modest, typically being 30–60% greater than control values at maximum, findings that are consistent with a large body (>10, 000) of hormetic dose/concentration responses not related to pre- and postconditioning. Regardless of the biological model, inducing agent, endpoint or mechanism, the quantitative features of hormetic dose/concentration responses are similar, suggesting that the magnitude of response is a measure of biological plasticity. This paper also provides the first documentation that hormetic effects account for preconditioning induced early (1–3 h) and delayed (12–72 h) windows of protection. These findings indicate that pre- and postconditioning are specific types of hormesis.